1999
DOI: 10.1046/j.1460-9592.1999.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevoflurane anaesthesia on recovery in children: a comparison with halothane

Abstract: We prospectively studied one hundred ASA physical status I-II children, ages six months to six years, undergoing myringotomy surgery. Children were randomly assigned to one of four anaesthetic groups receiving either halothane or sevoflurane for anaesthesia and oral midazolam premedication or no premedication. We found that children anaesthetized with sevoflurane had significantly faster recovery times and discharge home times than those who received halothane. Patients given oral midazolam premedication had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
3
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(141 citation statements)
references
References 26 publications
3
130
3
5
Order By: Relevance
“…3 Adding nitrous oxide to anesthesia with sevoflurane reduces the minimum alveolar concentration (MAC) of sevoflurane, meaning that lower concentrations of the anesthetic can be used, thereby reducing the incidence of postoperative agitation. 25 When compared with isoflurane, sevoflurane appears not just to increase the incidence of emergence agitation, but also to prolong the duration of that agitation, which is a problem that was detected in children maintained under anesthesia with sevoflurane, where the occurrence of the complication was 20%, compared with an incidence of 7% when isoflurane was employed.…”
Section: Inhaled and Intravenous Anestheticsmentioning
confidence: 99%
See 3 more Smart Citations
“…3 Adding nitrous oxide to anesthesia with sevoflurane reduces the minimum alveolar concentration (MAC) of sevoflurane, meaning that lower concentrations of the anesthetic can be used, thereby reducing the incidence of postoperative agitation. 25 When compared with isoflurane, sevoflurane appears not just to increase the incidence of emergence agitation, but also to prolong the duration of that agitation, which is a problem that was detected in children maintained under anesthesia with sevoflurane, where the occurrence of the complication was 20%, compared with an incidence of 7% when isoflurane was employed.…”
Section: Inhaled and Intravenous Anestheticsmentioning
confidence: 99%
“…Some authors have observed a reduction in preoperative anxiety, have found it easier to separate children from parents and have observed a reduction in agitation when midazolam is used as premedication, followed by sevoflurane as anesthetic. 3 However, some authors have observed that emergence time was prolonged when midazolam was used. 3,33 Combining midazolam with small doses of diazepam, for premedication, improved the quality of recovery, with reduced incidence of agitation after anesthesia with sevoflurane.…”
Section: Anesthetic Premedication and Adjuvant Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apesar de alguns estudos registrarem que o midazolam administrado por via oral no pré-operatório não prolonga o tempo de recuperação 38,52,53 , outras pesquisas, envolvendo crianças submetidas à adenoidectomia, mostraram aumento no tempo de despertar e de recuperação 54,55 . Lapin e col. 56 observaram que, apesar do aumento no tempo de recuperação, não houve retardo na alta hospitalar após o uso do midazolam como medicação pré-anestésica em crianças submetidas à amigdalectomia. Vários autores, utilizando doses entre 0,2 e 0,75 mg.kg -1 não encontraram complicações associadas ao uso do midazolam como medicação pré-anestésica 46,53,57,58 .…”
Section: · Midazolamunclassified